DNA-protein biomarkers for immunotherapy in the era of precision oncology - Binnari Kim; So Young Kang; Kyoung-Mee Kim (Korean Society of Pathologists & the Korean Society for Cytopathology, 2021)
The use of biomarkers to guide patient and therapy selection has gained much attention to increase the scope and complexity of targeted therapy options and immunotherapy. Clinical trials provide a basis for discovery of biomarkers, which can then aid in development of new drugs. To that end, samples from cancer patients, including DNA, RNA, protein, and the metabolome isolated from cancer tissues and blood or urine, are analyzed in various ways to identify relevant biomarkers. In conjunction with nucleotide-based, high-throughput, next-generation sequencing techniques, therapy-guided biomarker assays relying on protein-based immunohistochemistry play a pivotal role in cancer care. In this review, we discuss the current knowledge regarding DNA and protein biomarkers for cancer immunotherapy.